Spatial and temporal predictability drive foraging movements of coastal birds - Madeleine Foley; Kimberly A. Lato; Matthew Fuirst; Richard R. Veit; Robert M. Cerrato; Lesley H. Thorne (Movement Ecology)
Abstract Background Temporal and spatial predictability of food resources are critical to the foraging efficiency of central place foragers. While site fidelity is often assessed in this context, route fidelity, or the repeated use of the same path while traveling, and temporal aspects of habitat predictability have received less attention. We examined how the use of urban, coastal, and offshore habitats influenced spatiotemporal predictability in the foraging patterns of herring gulls (Larus argentatus) and great black-backed gulls (L. marinus). Since gulls show higher site fidelity when foraging in urban habitats, we predicted that these trips would also show higher route fidelity. Similarly, we predicted that gulls foraging in coastal habitats would adapt the timing of foraging trips relative to tides. Methods We analyzed GPS tracks of herring gulls (n = 79) and great black-backed gulls (n = 37)—between 2016–2022 from four nesting colonies whose surrounding areas varied in their degree of urbanization. Fréchet distance, which is defined as the repeated use of the same path while traveling, was used to assess route fidelity, within colonies and between habitat types. We also compared the consistency of foraging trip timing relative to tidal stage and day of week, respectively, across habitat types. Results Neither herring nor great black-backed gulls showed higher route fidelity in urban habitats. Herring gulls showed direct travel between urban foraging sites but revisited sites in different orders, suggesting that a mosaic map may be used to navigate between known urban foraging sites. Herring and great black-backed gulls that foraged at coastal sites exhibited patterns in trip timing in relation to the tidal cycle, with foraging primarily occurring at or around low tide. Herring gulls in urban environments foraged more on Fridays and weekends, possibly due to increased or altered human activities on these days. Conclusions Our results demonstrate the importance of spatial memory and spatiotemporal predictability of gull foraging habitats and highlight the extent to which gulls adjust their movements based on their foraging habitats.